Komunikasi Pemasaran CV Laktatridia Dalam Memasarkan Susu Kambing (Studi Kasus Komunikasi Pemasaran dalam Mengenalkan dan Meningkatkan Penjualan Susu Kambing di CV Laktatridia Ciwidey, Bandung) - Iis Saidah (KOM & REALITAS SOSIAL, 2011)
This research uses case study metode wich would give such as comprehensive description of all marketing communication of the CV Laktatridia, complete with its implementation and problems that they are facing in doing the marketing of the goats milk.The research decides that the main target objective of the marketing Laktatridia product which is developed under the name